Double shift, double stress: How female manufacturing managers cope with work–family conflict - Lisa C. Kinnear; Alicia Naidoo (SA Journal of Industrial Psychology, 2024)
Orientation: The conflicting demands of work and family contribute to individual stress levels, particularly for women because of gender stereotypes. The male-dominated and pressured environment of manufacturing and gendered expectations at home exacerbate of stress for women manufacturing managers.